Do marco interruptivo final (dies ad quem) do prazo prescricional para a cobrança do crédito tributário em execução fiscal - Arrais, Gustavo Guilherme (2014)
The intention of this dissertation is to get a general view about the last day of the limitation period in fiscal execution actions, describing, this way, the legal and jurisprudential scenario. It is justified for the needs of knowing the future behavior expected by the receiver of the norm, and the legal certainty inherent in law. Based on an assumption that law is a text belonging to the communicacional system, we assume that the norms must carry their message until the receiver of the communication. Likewise, we understand that the hierarchy of laws must be respected, by the supremacy of the Constitution compared to the others norms about this subject. The logical positivism is used as the methodological approach, especially Professor Paulo de Barros Carvalho theory. The result is an objective and logical analyses of the subject, and the correct identification of the problems of the law text used nowadays